Learning Scope of Python Coding Using Immersive Virtual Reality - Saleh, Abdulrazak Yahya; Goh, Suk Chin; Tei, Roselind; Othman, Mohd Kamal; Mohamad, Fitri Suraya; Chwen Jen, Chen (springer, 2021)
Programming is a highly sought-after technical skill in the job market, but there are limited avenues available for training competent and proficient programmers. This research focuses on evaluating an immersive virtual reality (VR) application that has been introduced in the field of Python learning, which uses the interaction technique and a user interface, allowing the novice to engage in VR learning. 30 participants were recruited for the evaluation purpose and they are divided into two groups--15 for Experiment I, and 15 for Experiment II. A questionnaire to evaluate the user interface was done in Experiment I, and a questionnaire to evaluate the novice’s acceptance of the VR application was given to the participants in Experiment II. Furthermore, interviews were conducted to collect detailed feedback from all the participants. From the results, it can be noted that the implemented interaction designs in this VR application are adequate. However, more interaction techniques can be integrated to increase the degree of immersive experience of the user in the application. Besides, the interface of the application is considered adequate and reasonable. Nevertheless, there is room for improvement in the aspect of usability and provide a higher level user experience. The novices’ acceptance level of the new proposed learning method is low; this might be due to the users’ fear of change-- a normal human behaviour in embracing new things in life. Therefore, a larger sample size is proposed to further investigate the novice’s acceptance of the new learning method by using an improved version of the VR application.